Transformational Leadership, Organizational Culture, and OCB on Hospital Employee Performance - Berti Anharita; Endang Suswati; Sugeng Mulyono (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study aims to examine the influence of transformational leadership and organizational culture on employee performance in regional public hospitals, with Organizational Citizenship Behaviour (OCB) serving as a mediating variable. A quantitative explanatory approach was employed using a survey. Data were collected from medical and non-medical employees using structured questionnaires. The analysis was conducted using Partial least squares structural equation Modelling (PLS-SEM) was used to evaluate the relationships among transformational leadership, organizational culture, OCB, and employee performance. The findings revealed that transformational leadership and organizational culture have positive and significant effects on employee performance. Both variables also positively influenced OCB, which subsequently strengthened employee performance. Furthermore, OCB plays a mediating role in the relationship between transformational leadership, organizational culture and employee performance. These findings indicate that improving employee performance in public hospitals is not solely dependent on formal managerial systems but also on voluntary employee behaviours reflected through OCB. This study contributes to the human resource management literature by emphasizing the strategic role of OCB as a behavioural mechanism linking leadership, organizational culture, and employee performance in healthcare organizations’ performance. However, the study was limited to a single regional public hospital and used a cross-sectional design, which may limit its generalizability.